Comparison of isogenic sorghums for two types of cytoplasm and general and specific combining aptitude. - Williams, Héctor; Rodríguez, Raúl (Agronomía Mesoamericana, 2016)
The purpose of this study was to compare estimates of relati ve general and specific combining ability effects on isogenic hybrids in two different cytoplasm types (A1 and A2), and observe the possibility of use the A2 system for the commercialproduction of sorghum hybrids. Genotypes were evaluated in ten environments located in northern Mexico. Grain yield, days to flowering, grain moisture content at harvest, plant height, panicle lenght and panicle excertion were recorded from the experiments. Combining ability was estimated ac-cording to the model suggested by Beil and Atkins in 1967. Although in all studied, the characteristics generally, the best SCA and GCA were for A2 cytoplasm, there was no relation between cytoplasm type and combining ability. These results indicate that A2 cytoplasm can be used for commercial hybrid sorghum seed production, as an alternative to Al cytoplasm.